Endogenous networks and international cooperation. (May 2016) - Gallop, Max B
The rise of social network analyses in the social sciences has allowed empirical work to better account for interdependencies among actors and among their actions. However, this work has been, to a large extent, descriptive: it has treated these actions as exogenous and immutable. In many cases these networks describe actions like alliance formation or trade – phenomena that are the outcome variables for programs of social scientific research. In this article, I attempt to account for both interdependencies and the endogenous nature of networks by incorporating formal theory, helping answer the question of how these networks arise by looking at the incentives of actors to form links with each other. I discuss the appropriate solution concept for a network formation game, and present an algorithm for finding the equilibrium of these networks computationally as well as ways to compare the theoretical networks to observed networks in order to evaluate the fit of the theory. I apply these methods to the study of international cooperation – a subject where both the interdependencies and purposive nature of actors must be accounted for. The theoretical network is able to reproduce a number of important observed characteristics. Still, there are more factors that must be accounted for if we want to understand how the network of international cooperation is formed.